Hội tụ thu nhập với nghị quyết đặc thù của các tỉnh, thành phố trực thuộc Trung ương - Lý Đại, Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The article analyzes the role of specific resolution on income convergence across Vietnam provinces over the 2010–2021 period. Based on cross-section and fixed-effect panel data regression, the research results show that the resolution enhances income convergence across provinces. On average, one province with a resolution has a higher rate of absorbing the income gap than the average of the province without a resolution. In particular, the difference reaches 0.206 as the ratio of one province's income over the leading one, i.e. Ho Chi Minh City in the data sample. Moreover, the resolution also strengthens the role of the initial income, quality of human resources, and infrastructure in the recent income convergence process.
Keywords: Income Convergence; Resolution; Economics of Province and Region; Cross-Section Regression; Panel Data Regression